Effects of Botulinum Toxin A on an Incisional Hernia Reconstruction in a Rat Model. Issue 6 (10th May 2021) - Kwon, Jin Geun; Kim, Eun Key
Abstract : Background: Although the effects of botulinum toxin A on hernia reconstruction have been consistently reported, few studies provide objective evidence. The authors aimed to compare the effects of chemical component separation with those of mechanical component separation, and with a combination of chemical and mechanical component separation, in a rat hernia model. Methods: Rats were divided into four groups: 1, control; 2, chemical component separation; 3, mechanical component separation; and 4, chemical and mechanical component separation. Four weeks after hernia induction, botulinum toxin A was injected into groups 2 and 4. Hernia repair was performed 2 weeks after chemical component separation when mechanical component separation was performed in groups 3 and 4. Pretreatment and posttreatment defect sizes, traction forces, intraabdominal pressure, and hernia recurrences were analyzed. Results: The defect size was significantly decreased in groups 2 and 4 after chemical component separation. The traction force was significantly smaller in groups 2 and 3 compared with the control group, and the effects of chemical and mechanical component separation were additive. The mean intraabdominal pressure was 16.83 mmHg in group 1, 10.67 mmHg in group 2, 10.17 mmHg in group 3, and 9.67 mmHg in group 4, thus showing significant reductions following chemical and mechanical component separation. Recurrence was observed in all six animals (100 percent) in groups 1 and 3, but in only one of six (17 percent) in groups 2 and 4. Conclusions: Preoperative botulinum toxin A significantly reduces hernia size (by 30 percent) and the traction force required to medialize the rectus abdominis. After hernia repair, chemical component separation decreases the intraabdominal pressure to a similar degree as mechanical component separation, but only chemical component separation appears to reduce hernia recurrence.